How to spend it: A proposal for a European Covid-19 recovery programme - Jérôme Creel; Mario Holzner; Francesco Saraceno; Andrew Watt; Jérôme Wittwer (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2020)
The Recovery Fund recently proposed by the EU Commission marks a sea-change in European integration. Yet it will not be enough to meet the challenges Europe faces. There has been much debate about financing, but little about the concrete projects that the EU should be investing in. We propose a 10-year, exteuro2 trillion investment programme focusing on public health, transport infrastructure and energy/decarbonisation. In a national pillar Member States would be allocated exteuro500 billion, focused on the hardest-hit countries and front-loaded. The larger European pillar would be devoted to finance genuinely European projects. We call for a strengthened EU public health agency that invests in health-staff skills, facilitating their flexible deployment in emergencies, and is tasked with ensuring supplies of vital medicines (Health4EU). We present costed proposals for two ambitious transport initiatives: a dedicated European high-speed rail network, with four-routes cutting travel times between EU capitals and regions in half, and, alternatively, an integrated European Silk Road initiative that combines transport modes on the Chinese model. In the area of energy/decarbonisation we seek to "electrify" the Green Deal. We call for the accelerated realisation of a smart and integrated electricity grid for 100%-renewable energy sources (e-highway), support for complementary battery and green-hydrogen projects, and a programme, modelled on the SURE initiative, to co-finance member-state decarbonisation and Just Transition policies.
urn:nbn:de:101:1-2020071015000829951592
Keywords: 330; Recovery Fund; European Green Deal; Just Transition; transport infrastructure; electricity transmission; public health; Covid-19; EU; investment